2023
DOI: 10.3390/nursrep13010033
|View full text |Cite
|
Sign up to set email alerts
|

Is the Triage System Welcomed in the Tertiary Hospital of the Limpopo Province? A Qualitative Study on Patient’s Perceptions

Abstract: A triage system in the emergency department is necessary to prioritize and allocate scarce health resources to the medical needs of the patients to facilitate quality health service delivery. This paper aimed to ascertain if the triage system is welcomed in the tertiary hospital of Limpopo Province by exploring patients’ perceptions in the emergency department in South Africa. A qualitative research approach was used in this study with descriptive, explorative, and contextual research design to reach the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Hence, many initiatives that recognise the local ways of knowledge and societal norms have been launched to tackle the negative perceptions and obstacles that communities encounter while seeking treatment for both HIV and TB. Research has shown that South African communities are guided by a variety of laws, principles, and ideologies, including Ubuntu [15]. Ubuntu is an African motto that emphasizes the importance of showing respect and compassion towards others [16].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many initiatives that recognise the local ways of knowledge and societal norms have been launched to tackle the negative perceptions and obstacles that communities encounter while seeking treatment for both HIV and TB. Research has shown that South African communities are guided by a variety of laws, principles, and ideologies, including Ubuntu [15]. Ubuntu is an African motto that emphasizes the importance of showing respect and compassion towards others [16].…”
Section: Introductionmentioning
confidence: 99%